THE EFFECT OF WORD CLUSTER STRATEGY ON THE READING COMPEHENSION OF THE SECOND YEAR STUDENTS OF SMPN 1 PANGKALAN LESUNG - Palupi Retno Wulan; Dahnilsyah Dahnilsyah; M. Syarfi M. Syarfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This pre-experimental study is aimed at finding out if there is a significant effect of Word Cluster teaching technique on the ability of the second students of SMPN 1 Pangkalan Lesung in comprehending descriptive texts. The design of the study is one group pre-test-treatment-posttest design. There are 3 classes in the second year. Class VIII B in the second semester of academic year 2018/2019 that consist of 30 students are chosen as the sample by using cluster random sampling technique. The instrument of the test is in the form of multiple choices which consist of 40 items about descriptive texts. To collect the needed data the treatments were conducted for six times. The students’ scores were analyzed by using SPSS (Statistical Package for the Social Sciences) version 23.00 for windows. The results of the data analysis show that the mean score of the pre-test is 57.50 and the mean score of the post-test is 63.41. It means that the value of t-test is higher than t-table (3.088>2.045). The alternative hypothesis (HI) of this study is accepted. In other words, there is a significant effect of Word Cluster teaching technique on the reading comprehension ability of the second year students of SMPN 1 Pangkalan Lesung. The implication of this finding is beneficial for the teachers in teaching and learning English especially in teaching reading.Key Words: Effect, Word Cluster, Reading Comprehension